Sugar industry press mud as alternate organic fertiliser source. (1st January 2012) - Khan, Muhammad Jamil; Khan, Muhammad Qasim; Zia, Muhammad Sharif
Organic materials are added to soil for improving soil physico-chemical properties. In the present study different doses of press mud along with NPK were applied to wheat crop in pot and field experiments. The increasing levels of press mud application improved soil physical conditions like increase in total porosity and reduced bulk density. Organic matter content, NPK, Fe, Mn, Zn and Cu content in soil also increased with the press mud application. ECe, pH and exchangeable Na percentage were reduced. Increasing levels of press mud application also increased wheat yield, yield components and crop nutrient utilisation. For realising near maximum wheat yield (95% relative yield) 40 tonnes press mud per ha -1 was found to be the optimum level.